A Multi-Wavelength Phase Retrieval With Multi-Strategy for Lensfree On-Chip Holography - Wang, Qinhua; Ma, Jianshe; Su, Ping (Frontiers in Photonics, 2022)
Due to convenient operation and robust imaging, multi-wavelength phase retrieval has been widely applied in lensfree on-chip digital holographic microscope (LFOCDHM). Nevertheless, the insufficient diffraction variation and small number of measurements on the LFOCDHM make it difficult to eliminate the twin image by multi-wavelength phase retrieval. We propose a multi-wavelength phase retrieval for LFOCDHM based on energy constraint, global update strategy and vector extrapolation acceleration. Simulations and experiments on the LFOCDHM show that our proposed method realizes efficient elimination effect and robust reconstruction with three wavelengths for illumination while maintaining fast convergence. More importantly, the proposed method is simple and non-parametric. It is believed that the proposed method could provide a promising solution for LFOCDHM.